Genome architecture and DNA replication in Haloferax volcanii - Marriott, Hannah (2018)
The archaeon Haloferax volcanii is used to study DNA replication and repair, and it is unique amongst cellular organisms as it is able to grow in the absence of DNA replication origins. There are four DNA replication origins on the main circular chromosome (including the integrated mega-plasmid pHV4) and one on each of the other mega-plasmids pHV1 and pHV3. Replication origins are normally required for the initiation of DNA replication, however H. volcanii is able to grow faster when all chromosomal origins have been deleted. Therefore, H. volcanii must utilise other methods of DNA replication such as recombination-dependent replication. The origin found on pHV3 cannot be deleted from the episomal mega-plasmid, whereas the origin can be deleted from episomal pHV4. The pHV3 mega- plasmid can be integrated onto the main chromosome, which allows the pHV3 origin to be deleted from the chromosome. The pHV1 mega-plasmid origin can be deleted from the episomal mega-plasmid, and the entire mega-plasmid can be lost from the H. volcanii cell. This generates a viable, healthy strain, which shows that the pHV1 mega-plasmid is non- essential. It was also found that the pHV1 mega-plasmid exists in H. volcanii as a 6x concatemer which is ~510 kb in size, which may explain the reason for being able to delete the origin. To further investigate the mechanisms that recombination-dependent replication may use, replication machinery (MCM and GINS) were tagged and expressed. Due to time constraints, interactions were not seen. The mcm gene was put under the control of a tryptophan inducible promoter. A strain lacking chromosomal origins and therefore primarily using recombination-dependent replication was shown to require more MCM than a wild-type strain.